Synthesis of all-carbon quaternary stereocentres of 2-oxindole derivatives employing asymmetric bifunctional phase-transfer catalysis and nucleophilic catalysis - LITVAJOVA, MILI (Trinity College Dublin. School of Chemistry. Discipline of Chemistry, 2018)
Asymmetric Phase-Transfer Catalysis (PTC) has been efficiently employed in the enantioselective SN2-type alkylation of highly challenging C,N-bis-acylated 2-oxindole derivatives. The alkylated 2-oxindole-derived products, bearing a newly generated all-carbon quaternary stereocentre, represent highly malleable synthetic targets in organic chemistry. We have shown for the first time that phase-transfer catalysed alkylation can be performed in the absence of a base, providing a water-rich solvent mixture and a chiral phase-transfer catalyst are used. The most efficient phase-transfer catalysts in this study were derived from cinchona alkaloids substituted with a bifunctional urea motif. This novel PTC methodology has been successfully applied in the synthesis of a bioactive spirooxindole target. Nucleophilic catalysis by anionic species, such as fluoride and acetate ions, has been demonstrated in the O- to C-acyl transfer of 2-oxindole-derived substrates. Such rearrangement leads to direct formation of all-carbon quaternary stereocentres. Tetrabutylammonium fluoride (TBAF) and tetrabutylammonium acetate (TBAOAc) proved to be among the most proficient catalysts in the rearrangement of the acetyl group of 2-oxindole derivatives. Enantioselective methanolysis of succinic anhydride has been effectively mediated by nucleophilic catalysis. The catalysts employed in this transformation were chiral quaternary ammonium fluorides generated in situ by anion exchange between the cinchona alkaloid-derived quaternary ammonium bromides and KF. Extensive catalyst screening revealed the importance of a bifunctional urea moiety in the catalyst framework and a substitution of the quinuclidine nitrogen atom of quinine with a benzyl unit bearing electron-withdrawing groups.
APPROVED